A new method for quantification of regional nitrogen emission - Deposition transmission in China. (15th April 2020) - Ma, Mingrui; Chen, Weihua; Jia, Shiguo; Chang, Ming; Zhong, Buqing; Wang, Xuemei
Abstract: The spatial-temporal pattern of N deposition has an important ecological impact on terrestrial ecosystems, providing a scientific background for the study of global changes. Based on the analysis method of spatial ellipse, we establish the standard deviation ellipse (SDE) center migration method to quantify the transport of regional deposition, and discuss the uncertainty of this method, which proves the feasibility of this method in characterizing the regional transport of nitrogen deposition. In October 2015, about 70% of the local emissions from the three regions in the Beijing-Tianjin-Hebei (BTH) region, the Yangtze River Delta (YRD) region and the Pearl River Delta (PRD) region are deposited to the ground (about 30% are located within the region and 40% are outside the region). The results show that native nitrogen from anthropogenic emissions in BTH area migrates to the southeast while there is a southwest migration relative to emission area in the YRD and PRD region. Compared with reduced nitrogen, oxidized nitrogen is more susceptible to transport. This phenomenon is mainly related to the strong atmospheric reactivity of ammonia in the atmosphere. The transport distance of nitrogen deposition in different areas is the BTH>YRD>PRD. The transmission impact from the BTH region is relatively bigger. It is pointed out that more attention should be paid to the control of oxidized nitrogen emerging from nitrogen deposition on the transport of external areas in China's core urban agglomeration. The government and relevant departments need to formulate corresponding measures to smooth the current situation of air pollution in China. Highlights: A new method was established to quantify the regional nitrogen emission - deposition transmission. Compared with the reduced nitrogen, the oxidized nitrogen has better regional transport capacity. The differences of nitrogen deposition transport in three urban agglomerations in eastern China were revealed.